A DFT survey of CH4 storage and separation from CH4 /X (X = H2, CO2, N2, CF4, he, ne, and Ar) gas mixtures on Ti/Sc decorated B40 fullerene - P. Mousavian; M.D. Esrafili (Results in Chemistry)
In the current study, first-principles calculations are used to determine the stability of B40 fullerene decorated with Sc or Ti atoms and its applications in storing and separating CH4 from gas mixtures. Our calculations indicate that the metal atoms are unlikely to cluster on the B40. Furthermore, the metal decorated B40 fullerenes can adsorb up to 24 CH4 molecules with a gravimetric density of about 35 %. The decorated B40 fullerenes are also useful for purifying CH4 from CH4 /X (X = CF4, N2, CO2, H2, He, Ne, and Ar) gas mixtures.